Students’ unwillingness to speak english in english language classroom as perceived by students and teachers at high schools in hanoi = sự không sẵn lòng nói tiếng Anh của học sinh trong lớp học tiếng Anh nhận biết bởi giáo viên và học sinh cấp 3 ở Hà Nội - Phùng, Thị Mai Phương (2020)
Students’ unwillingness to speak in English language classroom after nearly 10 years studying English at schools has become an urgent problem because of the demand for communication in English. This study investigates to what extent students at high schools in Hanoi remain unwilling to speak English. In addition, it finds out the reasons for students’ unwillingness to speak English as perceived by both students and teacher at 2 high schools in Hanoi. 181 students and 2 teachers from Cao Ba Quat high school and Yen Vien high school were invited to participate in the research. Both quantitative and qualitative data analysis methods were applied to the study. The perceptions of both student and teacher participants were investigated through multiple methods: questionnaires, interviews and stimulated recalls. After the questionnaires, data was analysed to chose participants for interviews and stimulate recalls. Findings from questionnaires showed that the extent to which students remain unwilling to speak English in English language classroom was not too high. However, the validity of the results from questionnaires was not proved. Data from interview and stimulated recall helped to find out the reasons for students’ unwillingness to speak English. As perceived by students, 10 reasons synthesized were: Low group cohesiveness, Lack of teacher support, Low risk-taking, Less tolerance of ambiguity, Lack of motivation, Fear of negative evaluation, Language anxiety, Unfamiliar Topic, Lack of interest, and Bad experiences. From teacher’s perceptions, individual characteristics, lack of teacher support, low risk-taking and language anxiety were affective factors.